Translating Linguistic and Situation-based Jokes from Arabic into English: An Integrated Approach - Mohammed Al-Kenani, Tawffeek Abdou Saeed (Al-Adab Journal, 2022)
Jokes have increasingly become the medium through which people in different Arab countries express their concerns. Social media platforms such as Facebook and Twitter are full of jokes tackling various spheres of life. Those jokes serve as a secure resort for people to raise issues they may not be able to express openly. The present study deals with the complications involved in the translation of Arabic jokes in general, and political jokes in particular into English. It sheds some light on the extent to which the translations of those jokes retain the force of their originals. The corpus of this study consists of 100 jokes that have been collected from different websites. The theoretical framework is eclectic, as it considers theories of translation and linguistics. It is based on Hans Vermeer's skopos theory (Nord, 1997; Reiss and Vermeer, 2014; Vermeer, 1989), and Halliday's theory of Systemic Functional Linguistics (SFL) (Halliday, 1985/1994). This study concludes that understanding a joke and then reproducing and translating it depends on a combination of linguistic and extralinguistic factors. The joke tellers may embrace various ideologies, and translators are required to be familiar with those ideologies to render the text adequately. The fidelity of translation will never be preserved unless all those aspects are taken into consideration.